Surface-Matrix Screening Identifies Semi-specific Interactions that Improve Potency of a Near Pan-reactive HIV-1-Neutralizing Antibody - Kwon, Young D.; Chuang, Gwo-Yu; Zhang, Baoshan; Bailer, Robert T.; Doria-Rose, Nicole A.; Gindin, Tatyana S.; Lin, Bob; Louder, Mark K.; McKee, Krisha; O’Dell, Sijy; Pegu, Amarendra; Schmidt, Stephen D.; et al. (Cell reports (Cambridge), 2018)
Highly effective HIV-1-neutralizing antibodies could have utility in the prevention or treatment of HIV-1 infection. To improve the potency of 10E8, an antibody capable of near pan-HIV-1 neutralization, we engineered 10E8-surface mutants and screened for improved neutralization. Variants with the largest functional enhancements involved the addition of hydrophobic or positively charged residues, which were positioned to interact with viral membrane lipids or viral glycan-sialic acids, respectively. In both cases, the site of improvement was spatially separated from the region of antibody mediating molecular contact with the protein component of the antigen, thereby improving peripheral semi-specific interactions while maintaining unmodified dominant contacts responsible for broad recognition. The optimized 10E8 antibody, with mutations to phenylalanine and arginine, retained the extraordinary breadth of 10E8 but with ∼10-fold increased potency. We propose surface-matrix screening as a general method to improve antibodies, with improved semi-specific interactions between antibody and antigen enabling increased potency without compromising breadth. [Display omitted] •Development of a surface-matrix screening approach to improve antibody function•Identified hydrophobic mutations that improved 10E8 interaction with HIV-1 membrane•Identified positively charged mutations that improved interactions with HIV-1 glycan•Optimizing semi-specific interactions can improve potency while maintaining breadth Antibodies could impact the treatment and prevention of HIV-1 if they were sufficiently potent to allow cost-effective delivery. Kwon et al. used a surface-matrix screening approach to improve the potency of antibody 10E8 by ∼10-fold. The improved antibody, 10E8v4-5R+100cF, has among the best breadth and potency of current HIV-1-neutralizing antibodies.